General hospitals and psychiatric hospitals in present: the panorama for Mental Health and perspectives (Research, Society and Development, 2022)
With the change in the care model for people with mental disorders after Law 10.216/2001, which legitimizes the Brazilian Psychiatric Reform, the number of psychiatric hospitals has decreased while other units have emerged as an alternative way of treating people who need hospitalization. The purpose of this article is to demonstrate the number of institutions (general hospitals and psychiatric units) with beds available for psychiatry. The methodology was based on an active search on the official website of the Registry of Health Establishments – CNES portal. The official management report’s view refers to acceptable data for states and regions. Although the results found in this study, for the coverage rates by state and even by region, seem to be primarily satisfactory, when analyzed by municipality, the panel becomes different. The numbers in all states indicate that municipalities are not being assisted, denoting the importance of considering the municipal spheres to better locate the problems of lack of services offered.